Ask Question
5 September, 11:48

Write the following equation in the general form Ax + By + C = 0. 2 x + y = 6 2x + y - 6 = 0 2x + y + 6 = 0 2x - y - 6 = 0

0
Answers (2)
  1. 5 September, 12:18
    0
    2x + y - 6 = 0

    given 2x + y = 6 (subtract 6 from both sides)

    2x + y - 6 = 0 ← in general form
  2. 5 September, 13:43
    0
    Option B

    Step-by-step explanation:

    We have to write the equation in the general form

    Ax + By + c = 0

    Equation is 2x + y = 6

    We subtract 6 on both the sides of the equation to convert in the standard form.

    2x + y - 6 = 6 - 6

    2x + y - 6 = 0

    where A = 2

    b = 1

    and c = (-6)

    Option B will be the answer.
Know the Answer?
Not Sure About the Answer?
Get an answer to your question ✅ “Write the following equation in the general form Ax + By + C = 0. 2 x + y = 6 2x + y - 6 = 0 2x + y + 6 = 0 2x - y - 6 = 0 ...” in 📙 Mathematics if there is no answer or all answers are wrong, use a search bar and try to find the answer among similar questions.
Search for Other Answers